Shifting Paradigms of Teaching and Learning English through Social and Electronic Media for the Students of General English Class in the Mofussil Area of Gujarat - Prof. Dr. Prakash V Vekaria (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The COVID catastrophe has produced the sea change in our day-to-day life and higher education system is not an exception. The most affected area is perhaps the education all across the world. The entire system has undergone many sweeps and shifts during past a year and half. Our classes in colleges and universities have seen empty benches with no students. The thing is that the teachers came forward with the solution of this bizarre phenomenon and found out the solution with the help of technology. On the other hand, the students remaining at their homes have started self-learning with the help of social and electronic media available to them. As far as the learning and teaching of English is concerned, there is a paradigm shift in the process of interaction with the help of Whatsapp, Facebook, YouTube, Google and other such platforms. The research in this direction shows that there is a lot of changes has been happening in the field of learning language and literature. The online classes have played a vital role as the students cannot attend offline classes. The words like online, live, join and leave the class are at the tip of our tongue now-a-days. The distribution of Tablets among college students by the government of Gujarat has helped them to familiarise with the new digital world. The teachers have also learnt many new things in online classes.